Application of Vibrational Power Flow to a Passenger Car for Reduction of Interior Noise - S.K. Lee (Shock and Vibration)
Reduction of structure-borne noise in the compartment of a car is an important task in automotive engineering. Transfer path analysis using the vibroacoustic reciprocity technique or multiple path decomposition method has generally been used for structure-borne noise path analysis. These methods are useful for solving a particular problem, but they do not quantify the effectiveness of vibration isolation of each isolator of a vehicle. To quantify the effectiveness of vibration isolation, vibrational power flow has been used for a simple isolation system or a laboratory-based isolation system. It is often difficult to apply the vibrational power flow technique to a complex isolation system like a car. In this paper, a simple equation is derived for calculation of the vibrational power flow of an isolation system with multiple isolators such as a car. It is successfully applied not only to quantifying the relative contributions of eighteen isolators, but also to reducing the structure-borne noise of a passenger car. According to the results, the main contributor of the eighteen isolators is the rear roll mount of an engine. The reduced structure-borne noise level is about 5dBA.